Boosted thermal conductance of polycrystalline graphene by spin-coated silver nanowires. (May 2019) - Lee, Woorim; Kihm, Kenneth David; Lee, Woomin; Won, Phillip; Han, Seonggeun; Lim, Gyumin; Pyun, Kyung Rok; Ko, Seung Hwan
Highlights: CVD synthesized graphene composites with spin-coated silver nanowires (AgNWs). Raman thermometry to measure the thermal sheet conductance G S of the composite. AgNWs widen the transport passages and for both phonons and electrons. AgNWs composites show the 113% enhancement in G S compared to pristine graphene. Abstract: Spin-coated silver nanowires (AgNWs) on graphene show a significantly improved thermal conductance of the composite in comparison with pristine graphene with no nanowires. CVD-synthesized graphene is transferred onto an 8-nm thin TEM grid substrate, and AgNWs (average diameter 150-nm and average length 30-μm) are chemically grown from an AgNO3 reagent solution. The AgNW bridging overrides the negative effect of the grain boundary scattering of the electron/phonon energy carriers propagating in the polycrystalline CVD graphene and ultimately enhances the grain-to-grain heat transport by widening their passages. This boosting contribution of AgNWs is quantitatively assessed by measurement of thermal conductance for synthesized AgNW/graphene composite samples. The Raman thermometry measurement locations are selected to be beside a single AgNW (G-1), two AgNWs (G-2), and three or more AgNWs (G-3), so that the effect of AgNW density can be examined. The average enhanced thermal conductance values for the three AgNW-laid graphene samples are 319.27 nW/K, 343.66 nW/K, and 455.26 nW/K, respectively.